A Bibliometric Analysis of Unemployment Takaful, Job Loss Protection, and Unemployment Insurance: Insights from the Scopus Database - Mohamad Yazis Ali Basah; Hisham Sabri; Khairil Faizal Khairi; Mazlynda Md Yusuf; Siti Nor Amira Mohamad; Nurul Atika Azzan (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA